2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346572
|View full text |Cite
|
Sign up to set email alerts
|

Extension of FRI for modeling of electrocardiogram signals

Abstract: Abstract-Recent work has developed a modeling method applicable to certain types of signals having a "finite rate of innovation" (FRI). Such signals contain a sparse collection of time-or frequency-limited pulses having a restricted set of allowable pulse shapes. A limitation of past work on FRI is that all of the pulses must have the same shape. Many real signals, including electrocardiograms, consist of pulses with varying widths and asymmetry, and therefore are not well fit by the past FRI methods. We prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Only a summary of the VPW-FRI method in [7] will be shown here for the sake of brevity and extensive discussions can be found in [2,3,7]. The VPW-FRI is an extension of the FRI sampling and reconstruction scheme which was designed for a certain class of parametric signals which are not bandlimited.…”
Section: Variable Pulse Width -Finite Rate Of Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a summary of the VPW-FRI method in [7] will be shown here for the sake of brevity and extensive discussions can be found in [2,3,7]. The VPW-FRI is an extension of the FRI sampling and reconstruction scheme which was designed for a certain class of parametric signals which are not bandlimited.…”
Section: Variable Pulse Width -Finite Rate Of Innovationmentioning
confidence: 99%
“…The pulse model allows VPW-FRI to model signals as a sum of pulses which can be compressed by calculating the four parameters associated with each pulse. For example in regular ECG [2,3] it has been shown that a single heartbeat with, various morphologies, can be modelled using seven pulses giving 28 parameters. Depending on the HR, this can lead to substantial compression subject to the sampling rate of the data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation